Evaluation of joint medical and nursing notes with preprinted prompts. Issue 4 (December 1997) - Robins, A; Gallagher, A; Rossiter, M A; Lloyd, B W
Abstract : OBJECTIVE: To determine the views of doctors and nurses about two recent innovations in the structure of case notes: the use of preprinted prompts and the use of joint medical and nursing notes. DESIGN: Questionnaire survey of all doctors and nurses working on the children's wards. SETTING: Children's wards in a district general hospital. MAIN OUTCOME MEASURES: Whether or not respondents wanted to return to traditional notes; positive and negative aspects of the two innovations. RESULTS: There was an 81% response rate. 45 of 48 respondents (94%) did not want to return to traditional notes. Positive features of joint notes that were identified included: promotes team work (21/48 respondents), improves access to information (14/48), and reduces duplication (14/48). Negative features included uncertainty about identity of writer (8/48) and incompletely filled in sheets (7/48). Positive features of preprinted prompts included: less information omitted (29/48), easier to read and find information (28/48), and quicker to write (21/48). Negative features included: not enough space (19/48) and clerking too mechanical (16/48). CONCLUSION: Advantages of both innovations outweighed their disadvantages to the extent that only three out of 48 respondents wanted to return to writing traditional notes.